PENGARUH LOGISTIC SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTYDI LOTTE GROSIR WARU DAN LOTTE GROSIR MASTRIP - Gary Grinaldy Halim; Fitri Novika Widjaja; Antonius Budhiman Setyawan (Perpustakaan Universitas Surabaya, 2018)
The purpose of this research is to know the difference of perception of logistic service quality level and the influence of logistic service quality to customer satisfaction and customer loyalty in Lotte Wholesale Waru and Lotte Wholesale Mastrip. To measure customer satisfaction and customer loyalty then used Logistic Service Quality which measured by 2 dimension that is Logistic Service Quality Operational and Logistic Service Quality Relational. In this causal research used quantitative approach by distributing questionnaires to 200 respondents divided by 100 respondents from Lotte Wholesale Waru and 100 Respondents from Lotte Wholesale Mastrip who is a customer in Lotte Wholesale Waru and Lotte Wholesale Mastrip. Data analysis technique used is anova test and multiple linear regression analysis.The result of the anova test shows that there is different perception of logistic service quality level at Lotte Wholesale Waru and Lotte Wholesale Mastrip, besides the result of research using multiple linear regression analysis is variable Logistic Service Quality have positive linear influence to Customer Satisfaction and Customer Loyalty.